1970
DOI: 10.1104/pp.45.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ethylene in Responses of Etiolated Bean Hypocotyl Hook to Coumarin

Abstract: Coumarin, at concentrations between 1.0 and 0.1 mM, inhibited red light-induced opening of the etiolated bean hypocotyl hook. In addition, anthocyanin synthesis and geotropic bending were inhibited. Coumarin stimulated ethylene synthesis, and ethylene was shown to mediate the inhibitory actions of coumarin. This conclusion was supported by: (a) the parallel concentration dependence and time sequence of hook closing and ethylene synthesis, (b) the restriction of the bulk of coumarin-induced ethylene production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…As reported for other plants (8,9), data presented in this paper demonstrated that ethylene could act as an inhibitor of light-stimulated anthocyanin synthesis in sorghum. The active ethylene concentrations were similar to those reported for other plant processes regulated by ethylene (10).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…As reported for other plants (8,9), data presented in this paper demonstrated that ethylene could act as an inhibitor of light-stimulated anthocyanin synthesis in sorghum. The active ethylene concentrations were similar to those reported for other plant processes regulated by ethylene (10).…”
Section: Discussionsupporting
confidence: 51%
“…Early observations by Kropfitsch (8) on Vicia faba indicated that ethylene inhibited anthocyanin synthesis in the nectaries but had no effect on anthocyanin development in the stem. Other reports have indicated that ethylene inhibits anthocyanin formation in bean seedlings (9) and that ethylene promotes anthocyanin synthesis in cranberry fruit (2). It was the purpose of this paper to determine the role of ethylene in light-induced anthocyanin synthesis in sorghum tissue.…”
mentioning
confidence: 99%
“…The first is the ability of DPX1840 to induce complete hook opening in Phaseoliis vulgaris L. and Pisuin sativumn L. seedlings in the dark where they would not normally open. Ethylene which is naturallv produced in the hook appears to play a regulatory role in maintaining the hook in a closed or reflexed position (22,23,38). The ability of DPX1840 to completely negate this effect of ethylene suggests that ethylene-mediated hook closure is dependent on a functional auxin transport system.…”
Section: Methodsmentioning
confidence: 99%
“…Rather, it alters the expression of the perceived stimulus, either at the level of transduction or response. For example, coumarin may simply enhance ethylene production, as has been observed in bean stem tissue (20). The local increase in cell expansion in the radial direction, then, may be indicative of the local ethylene level.…”
Section: Discussionmentioning
confidence: 99%